Kemampuan Komunikasi Matematis Mahasiswa melalui Pembelajaran Think Talk Write - Tina Sri Sumartini (Institut Pendidikan Indonesia, 2019)
AbstrakKemampuan komunikasi matematis perlu dimiliki mahasiswa untuk menyelesaikan masalah matematika. Peningkatan kemampuan komunikasi perlu didukung oleh pembelajaran yang tepat, diantaranya pembelajaran Think Talk Write (TTW). Tujuan penelitian ini yaitu menganalisis pencapaian dan peningkatan kemampuan komunikasi mahasiswa antara yang belajar dengan pembelajaran Think Talk Write dan konvensional, serta mengetahui interpretasi peningkatan kemampuan komunikasi mahasiswa dari kedua kelas. Metode penelitian yaitu kuasi eksperimen. Teknik pengambilan sampel dengan teknik Purposive Sampling dengan sampel sebanyak dua kelas di Program studi Pendidikan Matematika Institut Pendidikan Indonesia. Analisis data secara kuantitatif dengan uji gain ternormalisasi dan Mann Whitney. Hasil penelitian yaitu pencapaian dan peningkatan kemampuan komunikasi mahasiswa yang belajar dengan pembelajaran Think Talk Write lebih baik dari mahasiswa yang belajar dengan pembelajaran konvensional, peningkatan kemampuan komunikasi matematis mahasiswa yang belajar dengan pembelajaran Think Talk Write memiliki interpretasi tinggi sedangkan peningkatan kemampuan komunikasi matematis mahasiswa yang belajar dengan pembelajaran konvensional memiliki interpretasi sedang.Kata Kunci: Kemampuan Komunikasi Matematis, Think Talk Write, kuasi eksperimen Mathematical Communication Ability of Student through Think Talk Write LearningAbstractCommunication ability needs to be possessed by students to solve mathematical problems. Improved communication skills need to be supported by appropriate learning, one of which is learning Think Talk Write (TTW). The purpose of this study is to analyze the achievement and improvement of communication ability between students who are learning with Think Talk Write learning and conventional learning, as well as to find out interpretations of improved communication ability of students from both classes. The research method is quasi-experiment. The sampling technique is the purposive sampling technique by taking a sample of two classes in the Mathematics Education Study Program of the Institut Pendidikan Indonesia. Data analysis was performed quantitatively using the normalized gain test and Mann Whitney. The results of the study are the achievement and improved of communication skills of students who study with Think Talk Write learning is better than students who study with conventional learning, improvement of mathematical communication skills of students who study with Think Talk Write learning has a high interpretation while increasing mathematical communication skills of students who study with conventional learning have medium interpretations.Keywords: Mathematical Communication Ability, Think Talk Write, quasi-experiment